Ocular and systemic complement activation during anti-vascular endothelial growth factor treatment and age-related eye disease study 2 dietary supplementation in neovascular age-related macular degeneration - Altay, Lebriz; Lemke, Julia; Schröder-Braunstein, Jutta; Gietzelt, Caroline; Sitnilska, Vasilena; Schaub, Friederike; Cursiefen, Claus; Enders, Philip; Fauser, Sascha (Ophthalmologica, 2022)
Purpose: The aim of this study was to investigate the influence of dietary supplementation using Age-Related Eye Disease Study 2 (AREDS2) on complement activation in patients with neovascular age-related macular degeneration (nAMD) under ongoing treatment. Methods: In this prospective, single-center, controlled, open-label investigator-initiated trial, eligible nAMD patients were randomized at a ratio of 1:1 in 2 groups: those with and without dietary AREDS2 supplementation for 4 weeks. Zinc, plasma, and aqueous humor (AH) complement levels were quantified via enzyme-linked immunosorbent assays. Results: Fifty of 62 enrolled patients completed the trial (AREDS2 n = 27, controls n = 23). Systemic zinc and complement levels were not different at baseline between the 2 groups (p > 0.1). At the final visit, systemic zinc levels were significantly higher in the AREDS2 group (10.16 +/- 2.08 mu mol/L; 8.66 +/- 1.17 mu mol/L; p = 0.007), whereas systemic and AH complement levels were not different (p > 0.1). In both groups, no significant change was observed in systemic levels of C3, C3a, FH, FI, and sC5b-9 (p > 0.1). Only systemic complement component Ba showed an increase from baseline to the end visit (p = 0.01). This increase was higher in the control group (p = 0.02) than in the AREDS2 group (p = 0.23). Conclusions: Short-term dietary AREDS2 supplementation leads to a significant increase in systemic zinc levels without any influence on complement activation levels.
Gesehen am 10.11.2022